PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU DI PERGURUAN ADVENT PONAIN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This studynaims to determinenthe effect of work motivation on teachernperformance at the Ponain Adventist College, either partially or simultaneously. The population in this study were 50 teachers at the Ponain Adventist College and a sample of 50 respondents. Thentechnique used to collect data is byndistributing online questionnairesnusing google forms. The analysis usednis descriptive statisticalnanalysis, correlation coefficientnntest, coefficient ofndetermination test, and significant t test. In the descriptive statistics, it is found that the motivation indicator has the highest mean, namely the harmonious relationship with students, while the lowest mean is the observation of the principal. Regarding performance indicators, the highest mean is personal/individual factor, while the lowest mean is system factor. From the results of the correlation coefficient test, it was found that there was a strong relationship between motivation and performance seen from the rcount value of R = 0.787. The results ofnthe t-test of worknmotivation variables on employee performance are 8,847 > t table 2011 with a significancenvalue of 0.000 <0.05, fromnthese results partially motivational variables have ansignificant effect onnemployee performance.